The Drama of Possibility Experience as Philosophy of Culture - McDermott, John J. (Fordham University Press, 2022)
This book traces the trajectory of John J. McDermott's philosophical career through a selection of his essays. Many were originally occasional pieces and address specific issues in American thought and culture. Together they constitute a mosaic of McDermott's philosophy, showing its roots in an American conception of experience. Though he draws heavily on the thought of William James and the pragmatists, McDermott has his own unique perspective on philosophy and American life. He presents this to the reader in exquisitely crafted prose. Drawing inspiration from American history, from existentialist themes, and from personal experiences, he offers a dramatic consideration of our culture's failures and successes. McDermott crosses disciplinary boundaries to draw on whatever works to help make sense of the issues with which he is dealing-issues rooted in medical practice, political events, pedagogical habits, and the worlds of the arts. His work thus resists simple categorization. It is precisely this that makes his vibrant prose appealing to so many both inside and outside the world of American philosophy
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: PHILOSOPHY / General